Correlation of blood glucose levels, HbA1c, hemoglobin and leukocytes with outcome on acute stroke - ., Meiriani; Anwar, Yuneldi; Sinurat, Puji Pinta Omas (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes and higher HbA1c level have increased the incidence of stroke. Hemoglobin levels both high and low are associated with poor outcomes. Leukocytes play an important role in the initiation of the atherosclerosis process. Methods: This was a cross-sectional study with a sample size of 62 people selected by non-random sampling method on a consecutive basis, patients with acute stroke were taken blood to measure blood glucose levels, HbA1c, Hb and Leucocytes when entering the hospital room. Outcomes were assessed using NIHSS and MRS. The calculation of NIHSS and MRS scores was performed on the first day of admission and the fourteenth day. To analyze the correlation of blood sugar levels during HbA1c, Hb and leukocytes in acute stroke, this study used Spearman's correlation test. The p value <0.05 was considered statistically significant. Results: The study subjects of 62 acute stroke patients (acute ischemic stroke 31 people and 31 people hemorrhagic stroke). Acute stroke patients were consisted of 38 men (61.3%) and 24 women (38.7%). Of 31 people with hemorrhagic stroke, there were 16 men (51.6%) and 15 women (48.4%), ischemic stroke patients were consisted of 22 people (71, 0%) and women were 9 people. Spearrman repair test showed no symptoms between blood glucose levels, HbA1c, Hemoglobin and leukocytes with outcomes in acute stroke. Conclusions: There was no significant association between blood glucose levels, HbA1c, hemoglobin and leukocytes with outcomes in acute stroke.